Philosophy’s Independence in Modernity: The Temporality of Myth and "Equality of Intelligences" as Conditions for Cultivating the Philosophical Environment - Nekliudov, Nikita Konstantinovich; Shchepanovskaya, Siyana Vitalievna (Philosophy and Realistic Reflection, 2026)
Contemporary mass interest in self-improvement and mindfulness requires philosophy to solve the problems of a modern soul no worse than other initiatives in the field of mind ecology. However, professional philosophers lose the philosophy and reduce it, for example, to teaching critical thinking. It often turns into a market product and falls victim to oversimplification. This stems from the fact that contemporary philosophical practice often actualizes only the "logical" tendencies of philosophy, thereby merely sustaining the broader cultural orientation toward rationality, the other side of which, as we know, is the crisis of the symbolic. However, the philosophers tend to avoid including a mythopoetic philosophical tradition in their practice, as myth and symbol remain fundamentally unmanageable within modern culture, evoking deep-seated disquiet. Evidently, it is the rare unity of these two vectors that creates the mystery and hypnotism of philosophy and its great names. Thus, the main idea of the article is that the modern way of philosophy can be shaped by myth-symbolic temporality, which is excluded from contemporary philosophy at the institutional and communicative dimensions. This time-as-intensity (especially in its renewal qualities) has to be integrated into the philosophical event (which finds its sharpness in the linear time of history) in a non-reductive manner. This is no longer a purely theoretical perspective in which mythopoiesis is internalized or monologized, but the prospect of a new type of philosophical practice and communities, which we propose to understand as an environment of already-non-reflective openness to myth and symbol.